Molecular Typing by Polymerase Chain Reaction Sequence Specific Primers (PCR- SSP) of Human Leukocyte Class I and Class II Alleles in a Sample of Iraqi Visceral Leishmaniasis Patients - Mohymen(Ph.D.), Nidal Abdul; Qader (Ph.D.), Abdullah M.; Ad’hiah (Ph.D.), Ali H. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Objectives: This study aimed to investigate the association between HLA alleles and visceral leishmaniasis (VL) in a sample of Iraqi patients. Methods: A total of 30 patients were studied, in addition to 20 age, gender and ethnicity matched controls. All subjects were genotyped by polymerase chain reaction-sequence specific primers (PCR-SSP) method. Results: For HLA-class I region (A and B loci), only HLA-A*19 allele showed a significant (P = 0.031) decreased frequency in VL patients as compared with controls (13.3 vs. 45.0%), and such deviation was associated with OR and PF values of 0.19 and 0.37, respectively. At HLA-class II region, HLA-DRB1*03 and HLA-DQB1*02 alleles were significantly (P = 0.020 and 0.013, respectively) increased in VL patients (56.6 vs. 20% and 46.6 vs. 10%, respectively) as compared with controls. The OR of such two positive associations was 5.23 and 7.88, respectively, and the EF value was 0.46 and 0.41, respectively. In contrast, HLA-DRB1*02 (13.3 vs. 45.0%) and HLA-DQB1*03 (33.3 vs. 70.0%) were significantly (P = 0.031 and 0.023, respectively) decreased in patients. However, none of these differences remained significant after correcting the P value for the number of alleles tested at each locus. Conclusion: these preliminary data suggest that HLA alleles may have some role in aetiopathogenesis of VL, and this role can be in favour of susceptibility and/or protection.